Pengaruh Abdominal Strengthening Pada Perubahan Derajat Nyeri Low Back Pain Non-Spesifik Pada Perawat Rumah Sakit Fathma Medika - Rahman, Abdur; Pradita, Angria; Fau, Yohanes Deo; Fariz, Achmad (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: The aim of this study to evaluate abdominal strengthening exercise in pain management of low back pain non-specific. Methods: This study used a quantitative experimental quasi method with a one group pre-post test design. The study conducted in Fathma Medika Hospital, Gresik. Fifteen nurses in the inpatient department who work 7 hours in a day with low back pain and body weigh less than 65kg. Study participant received twelve treatment sessions of abdominal strengthening over a period three times a week. Outcome measures were a score of VAS. Results: For the 15 nurses were 9 women and 6 men, there were no differences at baseline in VAS. At the end of the interventions the group showed a reducing pain. The test result show that the t-count value of sig. 0,000>0,05 so it can be concluded that there is a change in the degree of pain before and after treatment. From the result of the study by giving abdominal strengthening, the abdominal muscles will be stronger to maintain work balance with the erector spine. Conclusion: it can be concluded that the abdominal strengthening exercise given has an effect of reducing pain in low back pain non-specific experienced.